Intensity of Gadget Use and Its Impact on Early Childhood Psychosocial Development: A Study in Rurat Communities in Indonesia - Khoirotus Silfiyah; Ika Novita Sari (Universitas Al-Hikmah Indonesia, 2026)
Technological transformation offers various conveniences when utilized appropriately and wisely. In fact, the portrait of gadget use is often misused, especially by children. This certainly impacts their development. The purpose of this study was to examine the impact of gadget use on the psychological development of early childhood. A qualitative approach was used, using interviews with 11 parents of children aged 10 to 5 years. The collected data was then analyzed using thematic analysis. The research findings indicate that gadget use in children begins at a very early age, with an intensity of 30 minutes to 6 hours per day. Although there are positive impacts such as improved verbal skills, introduction of basic concepts, and broadening of insight through educational content, negative impacts are found to be more dominant. Gadget use is seen to significantly impact various aspects of children's psychology. These negative impacts include tantrums, dependency, emotional dysregulation, decreased social skills, and imitation of inappropriate viewing behavior. This uncontrolled intensity of use has the potential to disrupt children's physical, cognitive, emotional, and social development in the long term. Thus, the urgency of this research emphasizes the need for close parental guidance and supervision when children operate gadgets, in order to optimize children's development according to their phase and needs.